Identifying molecular mechanisms and therapeutic targets in medulloblastoma - Marques, Rita Da Cunha Taborda Junqueiro (2024)
Medulloblastoma (MB) is a malignant pediatric brain tumor originating in the cerebellum, exhibiting significant heterogeneity across its subgroups. Sonic Hedgehog (SHH) MB, a particularly well characterized subgroup, arises from cerebellar granule neuron precursors, with aberrations in the SHH signalling pathway. Galectin 3 (GAL3) plays a critical role in tumor progression by modulating immune responses and cellular processes and is notably upregulated in SHH-MB. To elucidate the mechanisms underlying GAL3 overexpression in SHH-MB, a GAL3 Knockdown (KD) was performed in DAOY and tNES cell lines. Our results suggests that GAL3 reduction leads to the decreased in tumor homing capacity and growth, in vivo. Additionally, the study emphasises the correlation between GAL3 and the arginine metabolism, revealing that the GAL3 KD disrupts the expression of arginine transporters and the enzyme Argininosuccinate Synthase 1 (ASS1) in DAOY cell lines. The metabolic vulnerabilities of tumor cells, particularly in amino acid pathways, are a promising avenue for new therapies. One potential strategy is targeting GAL3 which, when combined with arginine depletion strategies, could significantly enhance treatment efficacy. For SHH-MB, this combination therapy offers hope for more effective outcomes, especially in pediatric patients, potentially minimizing harmful side effects.